Genetic studies in the recently divergent Eligmodontia puerulus and E. moreni (Rodentia, Cricetidae, Sigmodontinae) from Puna and Monte deserts of South America - Armella Sierra, Alicia Beatriz (2017)
Eligmodontia is a genus of phyllotine rodents adapted to arid environments with seven recognized species. The sister species E. puerulus and E. moreni are distributed in the adjacent highland Puna and lowland Monte deserts respectively, and show remarkable morphological and chromosomal differences. However, analyses of the cytochrome b gene showed important variability, without reciprocal monophyly between them. In order to study the evolutionary processes involved in the diversification of both taxa, we analyzed 1161 bp of the mitochondrial control region and flanking sequences (N = 60), as well as 759 bp of the first exon of the nuclear gene IRBP (N = 14). Individuals of both species from Jujuy, Catamarca and Mendoza Provinces of Argentina were previously karyotyped. Results showed that the mitochondrial sequences present high haplotype and nucleotide diversity within all population, and no haplotype was shared between both species. FST indicated that populations of both species were moderately structured. The network was constituted by two major haplogroups, one composed by E. puerulus samples from Jujuy, and the other composed of sequences of all studied populations. The Bayesian analysis showed three clusters, matching the network. Phylogenetic analysis recovered two clades with high support, in coincidence with the network groups. There was only one close join between sequences of both species, corresponding to samples from Catamarca. Thus, mitochondrial data suggested hybridization between both species in Catamarca, with asymmetric introgression. The IRBP showed low variability and, in the phylogenetic analysis, the sequences of E. puerulus form a monophyletic group with intermediate support, whereas those of E. moreni collapse into a basal polytomy. Our data indicated a recent divergence and absence of introgression in the nuclear genomes. The results at the population level with mitochondrial sequences, together with integrative taxonomy at the species level in a biogeographic context, suggest that climatic and geologic changes could have had an important role in the determination of genetic variability patterns observed in these rodents.